UV nanoimprint materials: Surface energies, residual layers, and imprint quality - Schmitt, Holger; Frey, Lothar; Ryssel, Heiner; Rommel, Matthias; Lehrer, C. (Journal of Vacuum Science & Technology B, 2007)
UV nanoimprint lithography is attracting more and more interest, because it has the potential of becoming a high-resolution, low-cost patterning technique. The availability of suitable UV curing materials is mandatory for successful imprinting. Within this work, a systematic investigation of commercially available photocuring materials was conducted to provide an overview of the properties of these materials. Their wetting behavior with respect to different substrate surfaces was characterized and their surface tensions were determined from their contact angles against two specifically selected solid surfaces: This method is presented here for the first time. The adhesion properties of the UV curing materials to different substrate surfaces and to the mold were investigated and necessary curing times were estimated. Additionally, the dependence of the residual layer thickness on the viscosity and the initial dispensed volume of UV curing materials was analyzed. It was found that the resist formulation of the UV curing materials strongly influences the surface tension as well as the adhesion to different substrate surfaces. Furthermore, the experiments verified that the thickness of the residual layer for UV curing materials increases with the square root of their viscosity which is predicted by theory. To demonstrate the suitability of the UV curing materials, first imprints with the prototype imprint tool, Nano Patterning Stepper 300 from Sbss MicroTec. with pattern sizes down to 50 nm are shown. (c) 2007 American Vacuum Societ